1993
DOI: 10.1128/jvi.67.4.2344-2348.1993
|View full text |Cite
|
Sign up to set email alerts
|

Passive antibody protection of cats against feline immunodeficiency virus infection

Abstract: All six cats passively immunized with sera from either feline immunodeficiency virus (FIV)-vaccinated cats or cats infected with FIV (Petaluma strain) were protected from homologous FIV infection at a challenge dose that infected all six control cats. Passive immunization with sera from cats vaccinated with uninfected allogeneic T cells used to grow the vaccine virus did not protect either of two cats against the same FIV challenge. These results suggest that antiviral humoral immunity, perhaps in synergy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Inactivated preparations of the Petaluma isolate have successfully protected cats against experimental infection with homologous and slightly heterologous (11% amino acid difference in surface Env) FIV isolates, (8,31,32). However, the same vaccines were unable to protect cats against challenge infection with heterologous FIV isolates which differed by 20% in the surface Env region (12).…”
mentioning
confidence: 99%
“…Inactivated preparations of the Petaluma isolate have successfully protected cats against experimental infection with homologous and slightly heterologous (11% amino acid difference in surface Env) FIV isolates, (8,31,32). However, the same vaccines were unable to protect cats against challenge infection with heterologous FIV isolates which differed by 20% in the surface Env region (12).…”
mentioning
confidence: 99%
“…However, Yamamoto et al reported the induction of protective immunity in cats against homologous and to a lesser extent also to heterologous FIV challenge, by vaccination with inactivated whole virus or FIV-infected cells (49,50). This protective effect could be transferred to naive cats with plasma from vaccinated animals, indicating that antibodies may be at the basis of this protective immunity (13). It was shown that serum antibodies against FIV envelope glycoproteins, with different VN domains, correlated more with protective immunity than did antibodies to other viral proteins.…”
mentioning
confidence: 99%
“…Another possibility is that cell-mediated responses rather than humoral factors are critical for defending against FIV. Attempts to transfer protection against lentiviruses by means of passively administered antibodies obtained from vaccinated hosts have provided contradictory results (2,9,12,33,40,44) and in one study have even accelerated FIV challenge infection (69). Our prior studies have failed to find a correlation between FIV-specific T-cell-proliferative responses of PBMC from vaccinated cats and protection (47,48); however, the role of FIV-specific cytotoxic T lymphocytes induced by vaccines is under scrutiny (22,23,35,74).…”
Section: Discussionmentioning
confidence: 99%